PERBEDAAN PENGGUNAAN SERUM DAN PLASMA EDTA (Ethylene Diamine Tetraacetic Acid) TERHADAP HASIL PEMERIKSAAN WIDAL METODE KUANTITATIF: Bahasa Indonesia - Magfirah M. Taepo; Budi Santosa; Meutia Srikandi Fitria (LPPM Universitas Abdurrab, 2025)
Widal examinaton is an agglutination test used in the serological diagnosis of typhoid fever. Widal examination consists of two methods, namely qualitative and quantitative methods. Specimens that can be used for serological tests are serum, plasma and cerebrospinal fluid. The plasma used is EDTA plasma. The purpose of this study was to determine the differences in the use of serum and EDTA plasma on the results of the quantitative method of Widal examination. This study was conducted at the Clinical Pathology Laboratory of Roemani Hospital, Semarang. This type of research is an analytical study with a cross-sectional approach conducted from October to November 2024. The samples studied were 16 serum samples and 16 EDTA plasma samples. The results of the Widal examination using serum obtained low titer results of 1/80 in 11 samples (34.4%), medium titer 1/160 in 16 samples (50%) and high titer 1/320 in 5 samples (15.7%) with a research sample of 32 (100%), while in plasma obtained low titer results of 1/80 in 26 samples (81.3%), medium titer 1/160 in 5 samples (15.7%) and high titer 1/320 in 0 samples (0%) with a research sample of 32 (100%). The results of the study showed that there were differences in the results of the Widal examination using serum and EDTA plasma on the results of the Widal examination.